SPECIFICS OF DEVELOPMENT AND COURSE OF ACUTE CORONARY INSUFFICIENCY DURING EXTREME HEAT WEATHER CONDITIONS - A. A. Garganeeva; E. A. Kuzheleva; V. P. Gorbatenko; S. A. Okrugin; I. V. Kuzhevskaya (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To evaluate the specifics and dynamics of acute coronary pathology in the period of the year with anomaly hot weather.Material and methods. The study is based upon integration of clinical and epidemiological data from the “Registry of acute myocardial infarction” with meteorological data by Tomsk city for last 25 years. Taken the weather report data, summer months of 2012 were taken for further assessment on myocardial infarction (MI) course in extreme weather heat. Into the study, all patients included that had MI in summer of 2012 and registered in the “Acute MI Registry” (n=241). Comparison group consisted of MI patients in the 2010 summer (n=198).Results. The part of females increased, as of senile and older age persons, among the cohort of MI patients during the heat. The increase of the number found, of atypical acute coronary pathology course at extreme weather conditions. In 2012, MI developed more frequently in those drunk or at the next day, comparing to 2010. All-cause mortality among all MI patients was registered in several days of the heat wave beginning. During anomaly hot period mortality rate was comparable with the time frames of similar mean temperatures, and after the end of the heat wave, mortality tended to decline, mostly by reduction of sudden cardiac deaths.Conclusion. Adverse tendencies in mortality and morbidity of MI are being registered in several days before the onset of anomalous heat. Taken that on-time healthcare influence is depended on the correctness of weather forecast, it is impossible to perform situational prevention events in response to the onset of extreme weather conditions, which demands for the long-term type organizational activities. Development of MI in alcohol intoxication or after this, as the high number of atypical clinical forms of MI demands for the improvement of information in general population.